2003
DOI: 10.1136/thorax.58.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Self-management of asthma in general practice, asthma control and quality of life: a randomised controlled trial

Abstract: Background: A study was undertaken to determine the effectiveness of asthma self-management in general practice. Methods: Nineteen general practices were randomly allocated to usual care (UC) or self-management (SM). Asthma patients were included after confirmation of the GP diagnosis. Follow up was 2 years. Patients kept diary cards and visited the lung function laboratory every 6 months. Outcomes were number of successfully treated weeks, limited activity days, asthma specific quality of life, forced expirat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(59 citation statements)
references
References 20 publications
1
58
0
Order By: Relevance
“…A study using the same self management plan as in the present study showed a saving of more than 200 puffs of ICS per patient over a period of two years in favour of the self management compared to the 'usual care' group [9]. A significantly higher proportion of subjects from the self management group took domestic HDM avoidance measures.…”
Section: O P Y R Ig H T G E N E R a L P R A C T Ic E A Ir W A Y S Gsupporting
confidence: 57%
See 2 more Smart Citations
“…A study using the same self management plan as in the present study showed a saving of more than 200 puffs of ICS per patient over a period of two years in favour of the self management compared to the 'usual care' group [9]. A significantly higher proportion of subjects from the self management group took domestic HDM avoidance measures.…”
Section: O P Y R Ig H T G E N E R a L P R A C T Ic E A Ir W A Y S Gsupporting
confidence: 57%
“…Most participants used budesonide 200 g via Turbuhaler ® . Details of this plan are described by Thoonen et al [9]. In Box 1 a summary of the self management plan is shown.…”
Section: Medication Usementioning
confidence: 99%
See 1 more Smart Citation
“…2,5,6,9,10 The few studies that did examine subjects' reasons for using self-management strategies reported explanations such as having a fixed daily routine and following the advice given by their doctor. 11 Reasons for not using self-management strategies included forgetfulness, belief that the medication was ineffective, not feeling any benefit, lack of perceived symptoms, denial that they have asthma, difficulty in using inhalers, inconvenience, fear of adverse effects, embarrassment, and laziness.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] However, patients' reasons, perceptions, and behaviors in relation to using (or not using) self-management diaries remain largely unknown. Because existing studies 2,5,6,[9][10][11][12][13][14] are limited in scope and setting and focus merely on the subject, thus neglecting the role of the caregiver, the findings of these studies may not be transferable between patient types and settings. The aim of this qualitative study was to understand health-care professionals' and subjects' perceptions and behaviors related to selfmanagement diary use.…”
Section: Introductionmentioning
confidence: 99%